Patient-reported financial toxicity in multiple sclerosis: Predictors and association with care non-adherence. (March 2021) - Sadigh, Gelareh; Lava, Neil; Switchenko, Jeffrey; Duszak, Richard; Krupinski, Elizabeth A; Meltzer, Carolyn; Hughes, Danny; Carlos, Ruth C
Background: Multiple sclerosis (MS) results in considerable financial burdens due to expensive treatment and high rates of disability, which could both impact care non-adherence. Objective: To measure financial toxicity in MS patients, identify its predictors and association with care non-adherence. Methods: Adult MS patients visiting neurology clinic (June 2018 to February 2019) were consented to complete a survey. Financial toxicity was measured using Comprehensive Score for Financial Toxicity (COST) (range: 0–44, the lower the score, the worse the financial toxicity). Independent predictors of financial toxicity were identified using linear regression. Associations of COST score with patient outcomes were assessed. Results: The mean COST score in 243 recruited patients was 17.4 ± 10.2. In response to financial burdens, 66.7% and 34.7% reported life-style altering behaviors or care non-adherence, respectively. Higher financial self-efficacy was associated with less financial toxicity (coefficient, 1.33 (95% confidence interval (CI), 1.02–1.64); p  < 0.001). At least one relapse in the last 3 months was associated with greater financial toxicity (coefficient, −3.34 (95% CI, −6.66 to −0.01); p  = 0.049). Greater financial toxicity correlated with life-style-altering coping strategy use ( p  < 0.001), care non-adherence ( p  = 0.001), and worse health-related quality of life (HRQOL) ( p  = 0.03). Conclusion: MS patients with lower financial self-efficacy and prior relapse history are at higher risk for financial toxicity, with associated care non-adherence and lower HRQOL.